Management - Stoner, James A. F; Freeman, R. Edward; Gilbert, Daniel R. (Prentice Hall, 1995)
This edition continues its strong research orientation and solid theoretical underpinnings. The general theme of the sixth edition is dynamic engagement - a broad term that captures the essence of change confronting future managers, and current thinking on what they will need to succeed. The material presented revolves around the themes of ethics, globalization, entrepreneurship and small businesses, cultural diversity, and quality. This work is appropriate for students following courses in the Principles of Management.